The Mortgage Rate Conundrum - Justiniano, Alejandro; Primiceri, Giorgio E.; Tambalotti, Andrea (Journal of Political Economy, 2022)
We document the emergence of a disconnect between mortgage and Treasury interest rates in the summer of 2003. Following the end of the Federal Reserve expansionary cycle in June 2003, mortgage rates failed to rise according to their historical relationship with Treasury yields, leading to significantly and persistently easier mortgage credit conditions. We uncover this phenomenon by analyzing a large dataset with millions of loan-level observations, which allows us to control for the impact of varying loan, borrower and geographic characteristics. These detailed data also reveal that delinquency rates started to rise for loans originated after mid 2003, exactly when mortgage rates disconnected from Treasury yields and credit became relatively cheaper.